Academic Freedom and Self-Actualization of Teachers in a Higher Education Institution - Elvenne Manila-Bate (PT FORMOSA CENDEKIA GLOBAL, 2023)
cademic freedom is very important in the performance of duties of the teachers. The study was undertaken to determine how academic freedom affects the self-actualization of the teachers of Palompon Institute of Technology and sought to find out the respondents’ level of understanding and extent of practice of academic freedom; level of self-actualization as well as the significant difference in the level of understanding and extent of practice of academic freedom when respondents are grouped according to their profile variables, significant relationship between the level of understanding on academic freedom and its extent of practice, and the significant relationship between academic freedom and self-actualization. Results of the study revealed that there is a significant difference in the level of understanding and extent of practice of academic freedom and self-